Analisis kemandirian belajar siswa dalam sistem pembelajaran jarak jauh di masa pandemi covid-19 di sekolah dasar - Nailufar, Yuyun; Marmoah, Sri Marmoah; Hadiyah, Hadiyah Hadiyah (Universitas Sebelas Maret, 2021)
Distance learning is a learning method used during the Covid-19 pandemic. In the learning process, teachers and students learn separately. The purpose of this study was to analyze student learning independence in the distance learning system during the Covid-19 pandemic. In this research, the research methodology uses descriptive qualitative, the subjects to be studied were the teachers and students of class VB SDN Dukuhan Kerten No. 58 Surakarta for the 2020/2021 school year with a total of 26 students.. Data collection techniques using observation, interviews, and questionnaires (questionnaires). The data validation used source and technique triangulation. Data analysis using data reduction techniques, data presentation, and drawing conclusions.From the research results, learning independence includes 5 indicators, namely self-confidence, discipline, responsibility, initiative in learning, and not depending on others. The highest indicators of independence are responsibility, then confidence, discipline, initiative in learning and the last one is not dependent on others. Distance learning that is carried out should be able to develop learning independence and be able to overcome obstacles amid existing limitations.